2020
DOI: 10.1039/d0tb00896f
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and design of soft polymeric bio-inspired materials with multiscale simulations and artificial intelligence

Abstract: Establishing the “Materials 4.0” paradigm requires intimate knowledge of the virtual space in materials design.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 265 publications
0
34
0
Order By: Relevance
“…The core of atomistic modeling lies in accurate and efficient techniques for numerically solving the Schrödinger equation for complex systems that consist of multiple atoms. [20,28] Examples of using DFT in materials science, and more specifically in materials design, include studying the formation of defects in metallic materials, [29][30][31] tailoring mechanical properties of alloys, [32][33][34] and polymeric materials design. [20,35,36] Using quantum mechanical calculation such as DFT to directly inform material research for AM is shown as the blue flow in Figure 2.…”
Section: Dft and High-throughput Dftmentioning
confidence: 99%
See 4 more Smart Citations
“…The core of atomistic modeling lies in accurate and efficient techniques for numerically solving the Schrödinger equation for complex systems that consist of multiple atoms. [20,28] Examples of using DFT in materials science, and more specifically in materials design, include studying the formation of defects in metallic materials, [29][30][31] tailoring mechanical properties of alloys, [32][33][34] and polymeric materials design. [20,35,36] Using quantum mechanical calculation such as DFT to directly inform material research for AM is shown as the blue flow in Figure 2.…”
Section: Dft and High-throughput Dftmentioning
confidence: 99%
“…[20,28] Examples of using DFT in materials science, and more specifically in materials design, include studying the formation of defects in metallic materials, [29][30][31] tailoring mechanical properties of alloys, [32][33][34] and polymeric materials design. [20,35,36] Using quantum mechanical calculation such as DFT to directly inform material research for AM is shown as the blue flow in Figure 2. For instance, in powder bed fusion (PBF) AM, the surface energies of different material phases drive the melt penetration phenomenon and strongly affect the quality of the resulting component.…”
Section: Dft and High-throughput Dftmentioning
confidence: 99%
See 3 more Smart Citations